In-hospital resuscitation: opioids and other factors influencing survival - Karamarie Fecho; Freeman Jackson; Frances Smith; et al (Dove Medical Press, 2009)
Karamarie Fecho1, Freeman Jackson1, Frances Smith1, Frank J Overdyk21Department of Anesthesiology, University of North Carolina, Chapel Hill, North Carolina, USA; 2Department of Anesthesia and Perioperative Medicine, Medical University of South Carolina, Charleston, South Carolina, USAPurpose: “Code Blue” is a standard term used to alertt hospital staff that a patient requires resuscitation. This study determined rates of survival from Code Blue events and the role of opioids and other factors on survival.Methods: Data derived from medical records and the Code Blue and Pharmacy databases were analyzed for factors affecting survival.Results: During 2006, rates of survival from the code only and to discharge were 25.9% and 26.4%, respectively, for Code Blue events involving cardiopulmonary resuscitation (CPR; N = 216). Survival rates for events not ultimately requiring CPR (N = 77) were higher, with 32.5% surviving the code only and 62.3% surviving to discharge. For CPR events, rates of survival to discharge correlated inversely with time to chest compressions and defibrillation, precipitating event, need for airway management, location and age. Time of week, witnessing, postoperative status, gender and opioid use did not influence survival rates. For non-CPR events, opioid use was associated with decreased survival. Survival rates were lowest for patients receiving continuous infusions (P < 0.01) or iv boluses of opioids (P < 0.05).Conclusions: One-quarter of patients survive to discharge after a CPR Code Blue event and two-thirds survive to discharge after a non-CPR event. Opioids may influence survival from non-CPR events.Keywords: code blue, survival, opioids, cardiopulmonary resuscitation, cardiac arrest, patient safety